THE DIRECT METHOD OF PREPARING CONSOLIDATED STATEMENTS. - Yankee, Glen G.; Green, David (The Accounting Review, 1961)
The subject area of "Consolidations" offers itself as a most suitable workshop for testing many of the notions of accounting. Yet the usual textbook solution involves so much busy work that the student has little remaining time or energy to benefit from theoretical inquiry. Indeed, the drudgery involved in the initial preparation of the worksheet may be sufficient to divert intellectual attention! Another obstacle to the learner is found in the multi-chapter approach to the subject found in many textbooks. With this approach, the student works largely with small discrete parts of the whole. Ordinarily this might be desirable; here, however, his attention is best directed to the whole problem since the answers to the parts are relevant only in the context of the whole. It is usually true that by the time a student undertakes the study of consolidations, he has an extensive and thorough background in accounting methodology and theory. The question as to the proper method for disposition of minority share of inter company profit of the three listed earlier is deliberately not raised here. Probably the answer relates to the purpose of the consolidated statements.